Good practice report : student transition into higher education. - Gale, Trevor; Parker, Stephen (Australian Learning and Teaching Council (ALTC), 2011)
Student transition into higher education (HE) is of considerable interest in the current policy context of equity and expansion targets for student participation and attainment in HE, recently announced by the Australian Government. This report reviews 19 completed projects funded by the Australian Learning and Teaching Council (ALTC) between 2006 and 2010, and identified by the ALTC as contributing to an understanding of student transition into HE. The summaries identify and analyse the findings of, and resources for, teaching and learning in HE particularly in relation to student transition. To enable a reading across these, each project/fellowship is summarised in six sections: (1) overview; (2) design, methodology; (3) findings, resources, outcomes; (4) dissemination; (5) implications for student transition into higher education; and (6) project report online availability. There are two interrelated observations regarding student transition into HE that have implications for teaching and learning. The first draws attention to HE as a distinct cultural context, while the second draws attention to the academic capital that governs this context. Together they focus on what students transition to rather than what they transition from and are premised on the implied benefits of making the transition. 1. Higher education: recognised as a distinct cultural context. 2. Higher education: governed by a distinct cultural capital. [Overview, ed]